Is DNA ploidy related to smoking? - Lima, Celina Faig [UNESP]; Alves, Monica Ghislaine Oliveira [UNESP]; Carvalho, Bruna Fernandes do Carmo [UNESP]; de Lima, Thaynara Alves [UNESP]; Coutinho-Camillo, Cláudia Malheiros; Soares, Fernando Augusto; Scholz, Jaqueline; Almeida, Janete Dias [UNESP] (Wiley, 2017)
Background: In the oral cavity, genomic instability is caused by long-term exposure to carcinogens. The aim of this study was to evaluate the relationship between smoking and DNA ploidy. Methods: Cytological material was obtained from patients participating in the Outpatient Smoking Treatment Program of the Heart Institute (INCOR-HCFMUSP), and of the Discipline of Oral Medicine (ICT-UNESP). The inclusion criteria for all groups were the absence of a history of malignant tumors, absence of clinical signs of changes in the selected area, and alcohol consumption of less than 3 units per week. Group 1:30 smokers before smoking cessation treatment; Group 2:30 non-smokers; Group 3:30 ex-smokers abstinent for at least 1 year. Cytological smears were collected from the floor of the mouth and border of the tongue and stained by Feulgen. Aneuploidy was evaluated using the ACIS® III system. Results: The Kruskal-Wallis test showed no statistically significant difference (P =.4383) between the groups studied. No association between tobacco consumption and aneuploidy was observed in group 1 (P = 1) or group 2 (P =.68; Fisher's exact test). Conclusion: Smoking was not associated with changes in DNA content or the incidence of aneuploidy in normal oral mucosa.
Keywords: aneuploidy; smoking; squamous cell carcinoma